Naive Diversification Strategies in Defined Contribution Saving Plans - Benartzi, Shlomo; Thaler, Richard H (American Economic Review, 2001)
There is a worldwide trend toward defined contribution saving plans and growing interest in privatized Social Security plans. In both environments, individuals are given some responsibility to make their own asset-allocation decisions, raising concerns about how well they do at this task. This paper investigates one aspect of the task, namely diversification. We show that some investors follow the “1/n strategy”: they divide their contributions evenly across the funds offered in the plan. Consistent with this naive notion of diversification, we find that the proportion invested in stocks depends strongly on the proportion of stock funds in the plan. (JEL G11, G23, H55)